Patronage and perceived efficacy of herbal antityphoid preparations, and anti-salmonella activity of a herbal preparation used in Ghana - George A Koffuor,Akua Afriyie Abruquah,Rauf Audu,John Amoah,Davina Agwah (Journal of Applied Pharmaceutical Science, 2016)
Objectives: To assess the patronage, and the perceived efficacy of herbal preparations in the treatment of typhoid fever, and to ascertain the anti-salmonella activity of a herbal preparation used as an antityphoid in Ghana. Materials and Methods: Purposively and conveniently from 700, 65 individuals who had had typhoid fever (clinically confirmed) were sampled. Well-structured questionnaires on the subject were administered to sampled individuals. Experimentally, the Minimum Inhibitory Concentration (MIC) of a herbal antityphoid preparation on Salmonella typhi was determined using the broth dilution method. Results: 46/65 (70.8%) used herbal preparations (19 used pre-packaged products; 27 used extemporaneous preparations) while 19/65 (29.2%) used orthodox drugs to treat their infection. Some of the herbs commonly used were Nauclea latifolia, Morinda lucida, Paullinia pinnata, Vernonia amygdalina, Cassia alata, Phyllantus fraternus, Azadirachta indica, Mangifera indica, and Carica papaya. Majority, 42/45 (91.3%), recovered after the use of the herbal anti-typhoid products (laboratory confirmation), 7/42 (15.2%) had relapse within three months, 9/45 (19.6%) experienced mild side effects. Experimentally, both the prepared herbal mixture and ciprofloxacin had MICs of 4 and 2 µg/µl respectively. Conclusion: Herbal anti-typhoid preparations are highly patronized and have been found to be efficacious. Experimentally the herbal mixture prepared showed interesting anti-salmonella activity.
Keywords: Broth dilution method, Ciprofloxacin, Minimum Inhibitory Concentration, Salmonella typhi, Vernonia amygdalina.